SEASONAL DISTRIBUTION OF SOME OCEANOGRAPHIC PARAMETERS OFF SOUTHWEST COAST OF INDIA RELEVANT TO PELAGIC FISHERIES - Murty, A V S; Vishnudatta, M N (Indian Journal of Fisheries, 2011)
Hydrographic condftions of the upper mixed layer play a dominant rolein the behaviour of the pelagic fishes and hence their fisheries. Murty (1965)studied the behaviour of the mixed layer and thermocline ofl the southwestcoast of India. Sharma (1966) correlated the seasonal changes of the level ofdiscontinuity layer with vertical motions (upwelling and sinking). Banse (1968)reviewed the hydrography of the region with a view to detecting the influenceof upwelling on the demersal fisheries. We make an attempt here to correlatethe pelagic fisheries for oil sardine and mackerel with temperature, salinity andoxygen conditions of the waters associated with the thermocline off the southwestcoast of India.